1979
DOI: 10.1002/aja.1001560117
|View full text |Cite
|
Sign up to set email alerts
|

The regenerating liver: A site of erythropoiesis in the adult long‐evans rat

Abstract: Erythropoiesis, which is primarily hepatic in the rat during fetal and early neonatal life, shifts almost entirely to the bone marrow in the neonatal-adolescent stage of development. In the adult, extramedullary erythropoiesis has been demonstrated in the liver and spleen under certain pathological conditions when bone marrow red cell production is insufficient. In the present study, erythropoietic foci have been found in young-adult rat liver regenerating 24-72 hr after subtotal hepatectomy. This erythropoies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…These results also implicate previous reports that several dedifferentiated hepatoma cell lines express hematopoietic cytokines (23,24). Moreover, regenerating liver was shown to express hematopoietic cytokines (25,26). Thus, expression of hematopoietic cytokines in the liver appears closely related to the state of liver differentiation, and OSM may be involved in regulation of hematopoietic cytokines in the adult liver as well.…”
Section: Discussionsupporting
confidence: 91%
“…These results also implicate previous reports that several dedifferentiated hepatoma cell lines express hematopoietic cytokines (23,24). Moreover, regenerating liver was shown to express hematopoietic cytokines (25,26). Thus, expression of hematopoietic cytokines in the liver appears closely related to the state of liver differentiation, and OSM may be involved in regulation of hematopoietic cytokines in the adult liver as well.…”
Section: Discussionsupporting
confidence: 91%
“…x 6,700 tion in the fetus. It is interesting that cases of liver hematopoiesis in the adult, as we have shown in the fetal rat, are sometimes characterized by nucleated red cells entering the peripheral circulation (Gunz, 1977;Naughton et al, 1979). Perhaps this indicates that the endothelial cell both in the fetal and the adult liver is incapable of differentiating between the maturational stages of the red cell with respect to diapedesis.…”
Section: Kupffer Cellsmentioning
confidence: 89%
“…We also reported that extramedullary hepatic hemaunder certain conditions. [1][2][3] In an in vivo experimental model topoiesis occurs only in close contact with LEC-1, suggesting of extramedullary hematopoiesis, we have reported the forthat these cells may provide the microenvironment necessary mation of hematopoietic colonies within the hepatic sinufor the maintenance and growth of hematopoietic cells. In the soids.…”
mentioning
confidence: 99%